Pericardium: An exceedingly rare site for a primary biphasic synovial sarcoma - Sarathchandra Kodikara (Wolters Kluwer Medknow Publications, 2012)
Pericardial neoplasms are rare. Among pericardial neoplasms, metastatic spread is more common and primary synovial sarcomas of the pericardium are exceedingly rare. A 61-year-old man was found dead in bed. Autopsy revealed the cause of death as atherosclerotic and hypertensive heart disease. There was a pericardial soft tissue mass lying predominantly over the left atrium. The cut surface was bulging out and grayish white in color with cystic changes. Microscopy showed spindle cells in densely cellular fascicles surrounding the epithelial cells. The epithelial cells were cuboidal and formed glandular structures and cleft-like spaces. Immunohistochemistry demonstrated cytokeratin and vimentin positivity in the spindled areas. Molecular analysis confirmed the diagnosis. Synovial sarcoma may be mistaken for other common neoplasms occurring in the pericardium due to its rarity. In all cases of pericardial tumors, a diligent search for synovial sarcoma by way of histological analysis including, immunohistochemistry and molecular analysis is indicated.